Small Group Communication Forming & Sustaining Teams - Castro, Moon (Open textbook library., 2021)
Small Group Communication: Forming & Sustaining Teams is an interdisciplinary textbook focused on communication in groups and teams. This textbook aims to provide students with theories, concepts, and skills they can put into practice to form and sustain successful groups across a variety of contexts.